HYDROCARBONOCLASTIC BACTERIA FROM JAKARTA BAY AND SERIBU ISLANDS - Darmayati, Yeti; Harayama, Shigeaki; Yamazoe, Atsushi; Hatmanti, Ariani; Sulistiani, -; Nuchsin, Ruyitno; Kunarso, Djoko Hadi (Marine Research in Indonesia, 2008)
Jakarta Bay has been known as one of the most polluted marine environment in Indonesia, with no exception by oil. Seribu Islands waters, located in the north of Jakarta Bay may have been impacted by this polluted condition.Itâs sometimes also hit by oil spillage from pipe leakage. The purpose of this study is to isolate and identify hydrocarbonoclastic bacteria (oil and Polyaromatic Hydrocarbon degrading bacteria) from Jakarta Bay and Seribu Island waters. The bacteria were isolated from water and sediment/sand. Isolation was prepared by enriched samples in SWP medium with Arabian Light Crude Oil (ALCO). Screening for PAH degrading bacteria has been completed by using sublimation plate method in ONR7a medium and screening for oil degrading bacteria were conducted by using oil plated method with the same medium. Bacteria identifications were done based on l6sRNA gene. The results were analyzed using BLAST and showed that 131 potential hydrocarbonoclastic bacteria have been isolated from Jakarta Bay and Seribu Island waters. Most of them were oil degrading bacteria (41.98%) and the rest were PAH degrading bacteria. Oil pollution level may impact the number of strain of hydrocarbonoclastic bacteria isolated. Among the hydrocarbonoclastic bacteria isolated from Jakarta Bay and Seribu Islands, Alcanivorax, Marinobacter, Achromobacter and Bacillus were common hydrocarbonoclastic genera in Jakarta Bay and its surrounding waters. Alcanivorax spp. is important oil and PAH-degrader found not only in temperate waters, but in tropical waters as well.